Applications of mechanical engineering mathematics : Solving Neumann problem with discontinuous coefficients. Issue 5 (4th July 2021) - Aghaeiboorkheili, Mohsen; Mohamed, Aezeden
Abstract: Neumann condition has so many applications in mechanical engineering. This paper suggests a numerical method for solving Neumann problem with discontinuous coefficients. The accuracy of mentioned method will be illustrated with some numerical examples with given exact solutions.